Plant dry weight and nutritive value of genetically diverse germplasm of false Rhodes grass [Leptochloa crinita (Lag.) P.M. Peterson and N.W. Snow], a native forage grass from arid regions of the Americas - Dominguez, Deolindo Luis Esteban (2021)
The native forage, false Rhodes grass [Leptochloa crinita (Lag.) P.M. Peterson and N.W. Snow], represents an important component of the arid and semi-arid rangelands of the Americas, due to its large area of distribution and its tolerance to drought and cattle grazing. Precise information on nutritive value and the factors that influence this trait is relevant for effective utilization as a forage in arid regions of the world. Here, we characterized dry matter (DM) per plant and nutritive value parameters in leaves, stems, and panicles of 21 genetically diverse L. crinita accessions, in a 2-yr partially replicated trial. Dry matter, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ash, fat, phosphorus, and calcium concentrations were determined. Significant (p <.01), substantial variation was found among accessions for DM, CP, NDF, ADF, ash, and fat content. Whole-plant DM varied ∼three-fold among the accessions. Variation was also found among the plant parts (p <.001) for all traits, with leaves and panicles having greater CP content than stems, and leaves being the less fibrous organs. In general, the range values found for DM (117–342 g DM plant−1), CP (76–109 g kg−1), NDF (747–839 g kg−1), and ADF (425–479 g kg−1) partially overlapped the range of variation reported for these traits in other forage grasses of arid regions, although some L. crinita accessions had greater CP and DM than most of the compared species; suggesting that L. crinita is an adequate forage grass for cattle grazing.